2020
DOI: 10.1186/s13550-020-0604-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative γ-H2AX immunofluorescence method for DNA double-strand break analysis in testis and liver after intravenous administration of 111InCl3

Abstract: Background: It is well known that a severe cell injury after exposure to ionizing radiation is the induction of DNA double-strand breaks (DSBs). After exposure, an early response to DSBs is the phosphorylation of the histone H2AX molecule regions adjacent to the DSBs, referred to as γ-H2AX foci. The γ-H2AX assay after external exposure is a good tool for investigating the link between the absorbed dose and biological effect. However, less is known about DNA DSBs and γ-H2AX foci within the tissue microarchitect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Hence, radiosensitive tumor cell lines retain phosphorylated H2A.X longer than radioresistant counterparts, making the former more sensitive to apoptosis than the latter [ 102 ]. In addition to various cells in vitro, γ H2A.X detection was also used to quantify the effects of IR in tissues exposed ex vivo or in vivo [ 109 , 110 ]. With a growing range of applications, γ H2A.X analysis expands beyond its traditional field of radiobiology, mainly because of its increasingly recognized role in ROS-related conditions.…”
Section: H2ax In Radiobiologymentioning
confidence: 99%
“…Hence, radiosensitive tumor cell lines retain phosphorylated H2A.X longer than radioresistant counterparts, making the former more sensitive to apoptosis than the latter [ 102 ]. In addition to various cells in vitro, γ H2A.X detection was also used to quantify the effects of IR in tissues exposed ex vivo or in vivo [ 109 , 110 ]. With a growing range of applications, γ H2A.X analysis expands beyond its traditional field of radiobiology, mainly because of its increasingly recognized role in ROS-related conditions.…”
Section: H2ax In Radiobiologymentioning
confidence: 99%
“…It allows us to visualize and quantify the presence and localization of significant proteins responsible for DNA damage, providing insights into its repair mechanisms and cellular processes. We have used a red fluorochrome-conjugated Alexa secondary antibody to see the expression of γH2AX with and without treatment related to DNA damage and cell death . We observed that 4T1 cells treated with CAAT NPs showed more significant red fluorescence than the untreated and AAT control groups due to the expression of γH2AX (Figure A,B).…”
Section: Resultsmentioning
confidence: 96%
“…We have used a red fluorochromeconjugated Alexa secondary antibody to see the expression of γH2AX with and without treatment related to DNA damage and cell death. 45 We observed that 4T1 cells treated with CAAT NPs showed more significant red fluorescence than the untreated and AAT control groups due to the expression of γH2AX (Figure 9A,B). From this observation, it can be suggested that CAAT NPs cause cell death by triggering DNA damage and apoptosis.…”
Section: ■ Introductionmentioning
confidence: 85%
“…foci can roughly re ect the number of DSB and was consistent with DSB at the beginning after irradiation. After a period of time, due to DNA repair, the numbers of γ-H 2 AX foci reduced and the expression level decreased(8, 9,22). Therefore, observing and counting γ-H 2 AX foci in irradiated cells was a widely used method to verify the presence of DSB in DNA and to analyze its repair (23).…”
Section: Discussionmentioning
confidence: 99%